Pharmacokinetic/pharmacodynamic relationships of FTY720 in kidney transplant recipients - Park,S.I. (2005)
FTY720 is a new and effective immunosuppressive agent, which produces peripheral blood lymphopenia through a lymphocyte homing effect. We investigated the relationship between the dose of FTY720 or blood concentration (pharmacokinetics, PK) and peripheral lymphopenia (pharmacodynamics, PD) in 23 kidney transplant recipients randomized to receive FTY720 (0.25-2.5 mg/day) or mofetil mycophenolate (2 mg/day) in combination with cyclosporine and steroids. FTY720 dose, blood concentrations and lymphocyte counts were determined weekly before and 4 to 12 weeks after transplantation. The effect of PD was calculated as the absolute lymphocyte count or its reductions. PK/PD modeling was used to find the best-fit model. Mean FTY720 concentrations were 0.36 ± 0.05 (0.25 mg), 0.73 ± 0.12 (0.5 mg), 3.26 ± 0.51 (1 mg), and 7.15 ± 1.41 ng/ml (2.5 mg) between 4 and 12 weeks after transplantation. FTY720 PK was linear with dose (r² = 0.98) and showed low inter- and intra-individual variability. FTY720 produced a dose-dependent increase in mean percent reduction of peripheral lymphocyte counts (38 vs 42 vs 56 vs 77, P < 0.01, respectively). The simple Emax model [E = (Emax * C)/(C + EC50)] was the best-fit PK/PD modeling for FTY720 dose (Emax = 87.8 ± 5.3% and ED50 = 0.48 ± 0.08 mg, r² = 0.94) or concentration (Emax = 78.3 ± 2.9% and EC50 = 0.59 ± 0.09 ng/ml, r² = 0.89) vs effect (% reduction in peripheral lymphocytes). FTY720 PK/PD is dose dependent and follows an Emax model (EC50 = 0.5 mg or 0.6 ng/ml). Using lymphopenia as an FTY720 PD surrogate marker, high % reductions (~80%) in peripheral lymphocytes are required to achieve best efficacy to prevent acute allograft rejection.